2021
DOI: 10.1182/bloodadvances.2021004846
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac toxicity after matched allogeneic hematopoietic cell transplant in the posttransplant cyclophosphamide era

Abstract: Graft-versus-host-disease (GVHD) is one of the leading causes of non-relapse mortality (NRM) following allogeneic hematopoietic cell transplantation (alloHCT). Post-transplant cyclophosphamide (PTCy) has shown promise in managing GVHD. However, cyclophosphamide has known cardiac toxicities and few studies have evaluated the cardiac toxicities that arise following PTCy. Here, we completed a retrospective analysis of matched alloHCT patients at our institution who received PTCy or non-PTCy-based GVHD prophylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 20 publications
1
25
2
Order By: Relevance
“…Longer follow‐up is needed to evaluate potential late events; however, it appears that PTCY is at least equally as effective as ATG in the prevention of GVHD‐related deaths. In contrast to ATG, the use of high doses of cyclophosphamide may be associated with severe organ complications, including cardiotoxicity and hemorrhagic cystitis 37,38 . However, in our study population, such events have not been reported as reasons for death.…”
Section: Discussionmentioning
confidence: 60%
“…Longer follow‐up is needed to evaluate potential late events; however, it appears that PTCY is at least equally as effective as ATG in the prevention of GVHD‐related deaths. In contrast to ATG, the use of high doses of cyclophosphamide may be associated with severe organ complications, including cardiotoxicity and hemorrhagic cystitis 37,38 . However, in our study population, such events have not been reported as reasons for death.…”
Section: Discussionmentioning
confidence: 60%
“…Pretransplant cardiac toxicity was reported to be associated with age >55 years, history of hypertension, arrhythmia, and diabetes, but this association was independent of GVHD prophylaxis used, contradicting earlier reported PTCY-based cardiac toxicity. 31 These findings are in contrast to the retrospective observation that patients treated with PTCY developed more cardiac events during the first 100 days posttransplant than patients in the non-PTCY group. 32 Using a composite risk model of cardiovascular comorbidities might further improve prediction of NRM, which has been reported recently.…”
Section: Discussionmentioning
confidence: 57%
“…Long-term HSCT survivors are also at increased risk for multiple cardiovascular risk factors such as hypertension, obesity, dyslipidemia, constrictive pericarditis, congestive heart failure, cardiomyopathy, conduction abnormalities, and valvular heart disease; prior chest radiotherapy increases the risk for many of these complications [ 43 , 55 ]. Recently, Yeh and colleagues reported cardiac comorbidities, older age, hypertension, diabetes, and arrhythmia were associated with increased risk for cardiac toxicity following HSCT; on the other hand, post-transplant cyclophosphamide was not [ 56 ].…”
Section: Resultsmentioning
confidence: 99%